The Product Rule of Exponents states that when multiplying two expressions with the same base, you can add the exponents. The general formula is:
\[ a^m \cdot a^n = a^{m+n} \]
In the case of the expression \(24^{12}\), we want to find two expressions with the base 24 that add up to 12.
-
\(24^4 \cdot 24^8\): Using the Product Rule, \(24^4 \cdot 24^8 = 24^{4+8} = 24^{12}\) — This is correct.
-
\(24^3 \cdot 24^4\): Using the Product Rule, \(24^3 \cdot 24^4 = 24^{3+4} = 24^{7}\) — This is incorrect.
-
\(6^4 \cdot 4^3\): This does not involve the base 24, hence it is irrelevant to simplifying \(24^{12}\).
-
\(12^4 \cdot 12^8\): Using the Product Rule, \(12^4 \cdot 12^8 = 12^{4+8} = 12^{12}\) — This is also incorrect since it does not involve 24.
The correct answer that correctly uses the Product Rule of Exponents to simplify to \(24^{12}\) is:
\(24^4 \cdot 24^8\).